2018
DOI: 10.1177/0974930618809173
|View full text |Cite
|
Sign up to set email alerts
|

Economic Analysis of Capital Expenditure and Infrastructural Development in Nigeria

Abstract: Infrastructural development has been the major concern of countries all over the world due to its significant impact in fostering growth. In Nigeria, it has been observed that the level of infrastructure posed serious threat to attaining sustained growth. This study therefore examines the impact of capital expenditure on infrastructural development in Nigeria, utilising time series from 1970 to 2017. The study adopted autoregressive distributed lag (ARDL) model due to the possibility of the past value of the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 12 publications
4
18
0
Order By: Relevance
“…Moreover, these two variables are cointegrated in the long run. The results of this research are comparable to the earlier ndings ofBabatunde (2018) andOkolo et al (2018) that spending on human capital development and infrastructure enhances growth with relative advantage.…”
supporting
confidence: 84%
See 1 more Smart Citation
“…Moreover, these two variables are cointegrated in the long run. The results of this research are comparable to the earlier ndings ofBabatunde (2018) andOkolo et al (2018) that spending on human capital development and infrastructure enhances growth with relative advantage.…”
supporting
confidence: 84%
“…Therefore, the relationship between trade openness, government expenditures and investment in infrastructure and economic growth have become, in recent years, the most important economic topics in both academic and policy circles from developed countries.Further empirical studies in developing countries especially Nigeria su ced the fact that trade openness does not determine economic growth, which indicated the absence of relative advantage due to lack of good environment and policies(Shayanewako, 2018). According to some scholars Babatunde (2018);Okolo et al (2018) andFauzel et al (2015) that government expenditure and investment in infrastructure seems a waste of scarce resources Ugochukwu et al (2021). observed that government failure to e ciently and equitably allocate resources for social and infrastructural development are most of the reasons for government to be fully involved in the economy.…”
mentioning
confidence: 99%
“…The results of the short run and long run indicated that government spending exerts a negative effect on economic growth. Okolo, Edeme, and Emmanuel (2018) examined the relationship between capital expenditure and infrastructural development in Nigeria using data for the period 1970 to 2017. The estimation was carried out using an Autoregressive distributed lag (ARDL) model.…”
Section: Public Expenditure and The Economy: An Empirical Reviewmentioning
confidence: 99%
“…The primary purpose of government, outside the provision of security, is to ensure the welfare of the people. This can mainly be achieved through public expenditure on infrastructure which stimulates the growth process of the economy and depends largely on the precise form and size of expenditure allocated to economic and social development projects (Okolo, Edeme & Emmanuel, 2018). Government's investment in such infrastructure is usually represented by the level of capital expenditure it incurs and is dependent on the level of funding it is able to generate.…”
Section: Introductionmentioning
confidence: 99%
“…Though budget on capital expenditure had generally been enormous over the years; the state of infrastructural facilities remains extremely poor with minimal improvements in roads; preponderance of ill-equipped educational and health institutions; high rate of unemployment and below average standard of living (Agunuwa and Nomuoja, 2016). Available data indicate that public expenditure had not contributed to infrastructure development due to low and inconsistent allocation with actual spending, in most cases, far below approved budgets (Okolo et al, 2018). The cost of governance given the first charge, mostly in the form of personnel costs and recurrent expenditure charged on accruable revenues, had left limited balances available for investment into social and other critical infrastructure.…”
Section: Introductionmentioning
confidence: 99%